Illicit drug use among university students in Lithuania: age, gender differences and correlation with lifestyle - Liudmila Rupšienė; Regina Saveljeva; Ingrida Baranauskienė; Aleksandra Batuchina (Social Welfare: Interdisciplinary Approach)
The article presents the research aiming at answering a question What is the illegal drug use among university students in Lithuania and what is its correlation with the age, gender and lifestyle? The research data was obtained from 18 Lithuanian universities involved in the research. The questionnaire’s questions were answered by 1087 students: 37 % male and 63 % female students. The average age of the respondents was 21 years; minimal age was 18, maximum was 29. The ESPAD questionnaire was adapted for the research. Some research results proved earlier results of research studies carried out in Lithuania; however, new tendencies significant to practice of prevention of drug use were revealed as well.